2019
DOI: 10.1093/mnras/stz2222
|View full text |Cite
|
Sign up to set email alerts
|

The subgiant HR 7322 as an asteroseismic benchmark star

Abstract: We present an in-depth analysis of the bright subgiant HR 7322 (KIC 10005473) using Kepler short-cadence photometry, optical interferometry from CHARA, high-resolution spectra from SONG, and stellar modelling using grids and the Bayesian grid-fitting algorithm . HR 7322 is only the second subgiant with high-quality Kepler asteroseismology for which we also have interferometric data. We find a limb-darkened angular diameter of 0.443 ± 0.007 mas, which, combined with a distance derived using the parallax from Ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 113 publications
1
22
0
Order By: Relevance
“…There is no obvious connection between these stars other than their best-fitting masses all being greater than 1.3 M . We also note that, at least in the Birmingham team's models, the dipole-mode frequencies are all increasing while the star's radius is staying roughly constant, as Stokholm et al (2019) also found for HR 7322. Because the star's mean density is therefore roughly constant, one would expect purely acoustic mode frequencies to be roughly constant too.…”
Section: Precise Age Estimatessupporting
confidence: 74%
See 2 more Smart Citations
“…There is no obvious connection between these stars other than their best-fitting masses all being greater than 1.3 M . We also note that, at least in the Birmingham team's models, the dipole-mode frequencies are all increasing while the star's radius is staying roughly constant, as Stokholm et al (2019) also found for HR 7322. Because the star's mean density is therefore roughly constant, one would expect purely acoustic mode frequencies to be roughly constant too.…”
Section: Precise Age Estimatessupporting
confidence: 74%
“…Such precise ages for subgiants and low-luminosity red giants have been encountered before (e.g. Deheuvels & Michel 2011;Ball & Gizon 2017;Stokholm et al 2019;Li et al 2020) but in most cases, the mass uncertainties are sufficiently precise that the age uncertainties are still consistent. We note, however, that Stokholm et al (2019) inferred very precise ages for the bright subgiant HR 7322 (KIC 10005473) and discuss the constraining power of its mixed modes in detail.…”
Section: Precise Age Estimatesmentioning
confidence: 71%
See 1 more Smart Citation
“…Using different approaches and input physics each team returned estimates of the physical properties of the star that were consistent to within 1 − 2σ, suggesting that the application of asteroseismic constraints produces more robust estimates of the stellar properties. For the mass and radius, which are typically well constrained by asteroseismology (Lebreton & Goupil 2014;Stokholm et al 2019), we adopted the overall values M = 1.16 ± 0.03 M and R = 1.63 ± 0.04 R . Together with a surface temperature of T eff = 5829 ± 80 K. Previous literature estimates suggest λ 2 For could be anything from an early G dwarf to a late G-type subgiant; however, multiple modeling teams using asteroseismic constraints all place the star firmly at the start of the subgiant phase of its evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This makes their seismic modeling challenging. Recently, increasing efforts have been made to model subgiants (Huber et al 2019;Stokholm et al 2019;Metcalfe et al 2020;Deheuvels et al 2020;Li et al 2019Li et al , 2020, driven by both their great physical interest and the sudden increase of seismic data for these stars. Most of those works focused on finding the optimal stellar parameters for one or several subgiants.…”
Section: Introductionmentioning
confidence: 99%